Efecto de la restricción alimenticia sobre el balance energético en pollos de carne criados a una altitud superior a 2 100 m.s.n.m. - Castro Salas, Jostin Andrés (2025)
Feed restriction is a common practice in poultry farming, as it allows for energy balance control. A reduction in dietary energy leads to decreased leptin expression and reduced abdominal fat. This study focused on analyzing the impact of qualitative and quantitative feed restrictions on the energy balance of broiler chickens raised at over 2,100 meters above sea level. Accordingly, the main objective was to examine the energy balance in broiler chickens subjected to quantitative and qualitative feed restriction programs. A total of 36 birds were used, distributed in groups of 12 per treatment. The sampling process was conducted randomly, selecting one bird per treatment and the experimental unit, along with two additional birds from randomly chosen replicates. The studied variables included energy intake, energy excretion, energy digestibility, retained energy, and apparent metabolizable energy. Quantitative and qualitative feed restriction did not produce significant differences in energy balance. This is attributed to the birds' innate ability to regulate feed intake. Similarly, energy intake and excretion showed no significant differences. These findings suggest that diet composition may influence energy consumption and excretion patterns.